Evodiamine via targeting nNOS and AMPA receptor GluA1 inhibits nitroglycerin-induced migraine-like response. (23rd May 2020) - Lin, Jiacheng; Zhang, Xu; Li, Chaotong; Zhang, Yingyan; Lu, Hanzhi; Chen, Jiwei; Li, Zeyu; Yang, Xuejun; Wu, Zhongping
Abstract: Ethnopharmacological relevance: Evodiamine (EVO) is a natural compound derived from Tetradium ruticarpum (A.Juss.) T.G.Hartley used to treat pain and migraine in traditional Chinese medicine. EVO is the primary active ingredient of Tetradium ruticarpum . However, the preventive effect of EVO against migraine remains unexplored. Aim of the study: To investigate the preventive effect of EVO against nitroglycerin (NTG)-induced acute migraine in rats. Materials and methods: Male Sprague-Dawley rats were intragastrically administered EVO (45 or 90 mg/kg) for nine days. To establish an acute migraine model, we subcutaneously injected rats with a 10 mg/kg NTG solution. The migraine-like behavior of the rats was evaluated via the formalin test and the warm water tail-withdrawal assay. The periaqueductal gray (PAG) and serum samples were collected from the rats and used to determine the effect of EVO on the levels of serum nitric oxide (NO), CGRP, c-Fos, neuronal nitric oxide synthase (nNOS), inducible nitric oxide synthase (iNOS) and the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor GluA1. Results: The formalin test and the warm water tail-withdrawal assay showed that EVO inhibited the licking foot/shaking response and reversed the shortened tail-withdrawal latency in NTG-treated rats. Additionally, EVO suppressed serum NO levels and reduced the mRNA/protein expression of c-Fos and nNOS, but not iNOS, in the PAG. Furthermore, EVO suppressed total protein expression of the AMPA receptor GluA1 and its phosphorylation at Ser831 and Ser845. Conclusions: This study showed that EVO inhibits the migraine-like pain response and that this beneficial effect might be attributed to the regulation of nNOS and suppression of the AMPA receptor GluA1. We suggest that EVO has the potential to treat migraine as a lead compound of natural origin. Graphical abstract: Image 1 Highlights: Evodiamine inhibits pain response and thermal hyperalgesia in the nitroglycerin-induced acute migraine rats. Evodiamine suppresses nitric oxide level and reduces neuronal nitric oxide synthase expression. Evodiamine suppresses AMPA receptor GluA1 expression. Nitroglycerin-injection increases total AMPA receptor GluA1 expression in the periaqueductal gray.